Comprehensive description of the Orion laser facility. (29th April 2015) - Hopps, Nicholas; Oades, Kevin; Andrew, Jim; Brown, Colin; Cooper, Graham; Danson, Colin; Daykin, Simon; Duffield, Stuart; Edwards, Ray; Egan, David; Elsmere, Stephen; Gales, Steve; et al.
Abstract: The Orion laser facility at the atomic weapons establishment (AWE) in the UK has been operational since April 2013, fielding experiments that require both its long and short pulse capability. This paper provides a full description of the facility in terms of laser performance, target systems and diagnostics currently available. Inevitably, this is a snapshot of current capability—the available diagnostics and the laser capability are evolving continuously. The laser systems consist of ten beams, optimised around 1 ns pulse duration, which each provide a nominal 500 J at a wavelength of 351 nm. There are also two short pulse beams, which each provide 500 J in 0.5 ps at 1054 nm. There are options for frequency doubling one short pulse beam to enhance the pulse temporal contrast. More recently, further contrast enhancement, based on optical parametric amplification (OPA) in the front end with a pump pulse duration of a few ps, has been installed. An extensive suite of diagnostics are available for users, probing the optical emission, x-rays and particles produced in laser-target interactions. Optical probe diagnostics are also available. A description of the diagnostics is provided.